Effect of depo-MGA on the prevention of pregnancy in grazing heifers - L.R. Corah; F.K. Brazle; G.W. Boyd; T. Goehring (Kansas Agricultural Experiment Station Research Reports, 1988)
Two field trials were conducted to evaluate various dosage levels of Depo-MGA® for preventing pregnancy in grazing heifers. Injecting Depo-formulated MGA subcutaneously in the ear at dosages of 60, 90 or 120 mg effectively prevented pregnancy for up to 135 days. There was no effect on average daily gain.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; MGA; Pregnancy; Heifers